2019
DOI: 10.1186/s12967-019-02138-5
|View full text |Cite
|
Sign up to set email alerts
|

Loss of alanine-glyoxylate and serine-pyruvate aminotransferase expression accelerated the progression of hepatocellular carcinoma and predicted poor prognosis

Abstract: BackgroundAccumulated studies reported abnormal gene expression profiles of hepatocellular carcinoma (HCC) by cDNA microarray. We tried to merge cDNA microarray data from different studies to search for stably changed genes, and to find out better diagnostic and prognostic markers for HCC.MethodsA systematic review was performed by searching publications indexed in Pubmed from March 1, 2001 to July 1, 2016. Studies that reporting cDNA microarray profiles in HCC, containing both tumor and nontumor data and publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…The same reaction has been reported to take place in peroxisomes (Poore et al, 1997). On the other hand, loss of alanine-glyoxylate aminotransferase (AGXT) expression has been reported to accelerate the progression of hepatocellular carcinoma (Sun et al, 2019). A "futile cycle" may exist between 3-PG and glycerate through 2-phosphoglyceric acid phosphatase and glycerate kinase 1 and 2; glycerate kinase 2 is also found in the mitochondria (Guo et al, 2006).…”
Section: Pathways Leading To Pyruvate Commencing From Glucose: Intermmentioning
confidence: 70%
“…The same reaction has been reported to take place in peroxisomes (Poore et al, 1997). On the other hand, loss of alanine-glyoxylate aminotransferase (AGXT) expression has been reported to accelerate the progression of hepatocellular carcinoma (Sun et al, 2019). A "futile cycle" may exist between 3-PG and glycerate through 2-phosphoglyceric acid phosphatase and glycerate kinase 1 and 2; glycerate kinase 2 is also found in the mitochondria (Guo et al, 2006).…”
Section: Pathways Leading To Pyruvate Commencing From Glucose: Intermmentioning
confidence: 70%
“…In Huh7- GCK + /HK2 − cells, increased levels of alanine-glyoxylate and serine-pyruvate aminotransferase ( AGXT ) could account for this phenotype as it converts alanine and glyoxylate into pyruvate and glycine, which is also increased. Interestingly, high level of AGXT is a good prognostic marker for HCC 41 . Consistently, it was found that oxalate inhibits liver PC, resulting in reduced gluconeogenesis and lipogenesis 42 , 43 .…”
Section: Discussionmentioning
confidence: 97%
“…Other genes of note were: Adora1, Serpine1, Themis, 10 Toll-like receptor ( Tlr ) genes , Spon2 and Zcchc11 ( Data S2 and Data S3 ). Among the downregulated genes, there is an enrichment in key enzymes of amino acid ( Gnmt, and Agxt ) and cholesterol metabolism such as HMG-CoA reductase ( Hmgcr ) which is implicated in liver disease and hepatocellular carcinoma ( 38 41 ) ( Fig. 3D ).…”
Section: Gene Expression Changes With Aging and Caloric Restrictionmentioning
confidence: 99%